Rizzio - Mina, Denise (Pegasus Crime, an imprint of Pegasus Books, Ltd, 2021)
"On the evening of March 9th, 1566, David Rizzio, the private secretary of Mary, Queen of Scots, was brutally murdered. Dragged from the chamber of the heavily pregnant Mary, Rizzio was stabbed fifty six times by a party of assassins. This breathtakingly tense novella dramatises the events that led up to that night, telling the infamous story as it has never been told before. A dark tale of sex, secrets and lies, Rizzio looks at a shocking historical murder through a modern lens--and explores the lengths that men and women will go to in their search for love and power"--Amazon.